2022
DOI: 10.1038/s41559-022-01773-4
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony and idiosyncrasy in the gut microbiome of wild baboons

Abstract: Human gut microbial dynamics are highly individualized, making it challenging to link microbiota to health and to design universal microbiome therapies. This individuality is typically attributed to variation in host genetics, diets, environments, and medications, but it could also emerge from fundamental ecological forces that shape microbiota more generally.Here we leverage extensive gut microbial time series from wild baboons-hosts who experience little interindividual dietary and environmental heterogeneit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 61 publications
3
67
0
Order By: Relevance
“…Our findings of weak long-term contributions of individual identity to gut microbial composition, an exponential decay in microbiota similarity within individuals over time, and increases in taxon repeatability with age, all align closely with those found in a decade long study of baboons [8,25], suggesting that such dynamics may be consistent across host species. These patterns in longitudinal dynamics may resolve the conflicting reports of the major drivers of gut microbiota dynamics across different species, with different findings being due to variable sampling intervals and designs rather than inherent differences among species.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings of weak long-term contributions of individual identity to gut microbial composition, an exponential decay in microbiota similarity within individuals over time, and increases in taxon repeatability with age, all align closely with those found in a decade long study of baboons [8,25], suggesting that such dynamics may be consistent across host species. These patterns in longitudinal dynamics may resolve the conflicting reports of the major drivers of gut microbiota dynamics across different species, with different findings being due to variable sampling intervals and designs rather than inherent differences among species.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, this does not preclude the possibility of differences in gut microbiota stability and associated drivers between host species. For example, individual host traits such as age, sex and social dominance rank generate individualized microbial signatures that are stable over short time frames in baboons [25], yet these traits do not have a strong stabilizing effect in meerkats [9].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study examined the gut microbiomes of baboons ( Papio spp.) over a 14-year period and concluded that although all gut microbiomes exhibited cyclical seasonal shifts in composition, microbiome dynamics across baboons were only weakly synchronized (14). Instead, baboons exhibited largely individualized gut microbiomes over their lifespans, despite their shared diets, environments, and opportunities for between-host microbial dispersal (14).…”
Section: Introductionmentioning
confidence: 99%
“…over a 14-year period and concluded that although all gut microbiomes exhibited cyclical seasonal shifts in composition, microbiome dynamics across baboons were only weakly synchronized (14). Instead, baboons exhibited largely individualized gut microbiomes over their lifespans, despite their shared diets, environments, and opportunities for between-host microbial dispersal (14). Findings from the two studies suggest that gut microbiome dynamics may be species-specific and influenced by host behavior, temporal factors, and habitat characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We also tested whether pairs of ASVs with especially consistent between-host correlation patterns tend to show large seasonal changes in CLR abundance. To do so, we focused on 13 families that exhibit significant seasonal changes in CLR abundance, based on a previous analysis of the same data set[42]. While ASV pairs in which one member belongs to one of these significantly "seasonal" families are slightly more universal, this effect is small (difference of 0.026, p<0.0001 vs. pairs where 0 or 1 partner were "seasonal"; Fig.S9).…”
mentioning
confidence: 99%